Aboriginal Employment: Improved in 2011, but still has a ways to go - Oppenheimer, Robert J. (Journal of Aboriginal Economic Development, 2012)
Employment is an important indicator of economic development. The Aboriginal employment rate in Canada increased to 55.8 in 2011, from 53.7 in 2010. This was an increase of 19,700 jobs. It increased more for Aboriginal men than for women in 2011. The strong relationship between higher levels of education and employment highlights a clear path for improving employment rates. Ontario experienced the greatest increase in employment with 8,800 new Aboriginal jobs in 2011, with employment growing in every province except Prince Edward Island, where it was flat. It was basically stable in the three territories. The sectors experiencing the greatest increases in employment were in retail trade and in manufacturing.